{Crustal stress and seismic activity in the Ionian archipelago as inferred by satellite- and ground-based observations, Kefallinìa, Greece} - Poscolieri, Maurizio; Lagios, Evangelos; Gregori, Giovanni P.; Paparo, Gabriele; Sakkas, Vassilis A.; Parcharidis, Issaak; Marson, Iginio; Soukis, Konstantinos; Vassilakis, Emmanuel; Angelucci, Francesco; Vassilopoulou, Spyridoula (Geological Society Special Publication, 2006)
Different observational techniques are compared in order to investigate possible correlations in seismic activity. The study site is the island of Kefallin_gnia (Greece), where measurements available included (1) DInSAR, DGPS, and DEM data, (2) soil exhalation measured by monitoring Radon (Rn) well content, and (3) acoustic emissions (AE) at high and low frequency (point-like records with high temporal resolution). AE records provide: (1) relative time variation of the applied stress intensity and (2) the state of fatigue of stressed rock volumes, the AE source. Our results indicate that the large spatial scale (poor time resolution) may be considered quite satisfactory, whereas fractal analysis of the AE time series displayed some discrepancies when compared to analogous investigations in the Italian Peninsula. Therefore, some refinement is needed in order to reach more precise interpretations of the relevant information available with this kind of data. However, both sets of observations appear in agreement with each other, although more exhaustive investigations would require a suitable array of point-like AE and Rn (or other) measuring sites, as well as longer data series. The latter are particulary helpful for detailed interpretations of the different occurrences within tectonically complex settings where crustal stress crises are marked by various types of geological phenomena. © The Geological Society of London 2006.